ABOUT THE NEW EDITION OF “DEVONI FONIY” - Sayfiddin Sayfulloh (International Journal of Literature and Language Studies, 2026)
Annotation.This study examines the Persian literary heritage of Alisher Navoi, particularly his Divan-i Fani, within the broader context of manuscript tradition, textual criticism, and editorial history. It traces the development of Navoi’s Persian works from early manuscript sources preserved in Paris, Tehran, and Istanbul to modern critical and annotated editions published in Uzbekistan, Tajikistan, and other scholarly centers. Special attention is given to the formation, structure, and genre composition of the Divan-i Fani, including ghazals, qasidas (Sittai Zaruriya and Fusuli Arbaa), muammos, rubaiyats, qit’as, and other poetic forms. The study highlights Navoi’s artistic method of tatabbuʿ, tavr, and original composition (mukhtaraʿ and ixtiroʿ), showing his creative engagement with major Persian poets such as Hafez, Saadi, Amir Khusrau Dehlavi, and Abdurahman Jami. The article also compares different textual versions and editions of the Divan-i Fani, identifying variations in manuscript readings, genre statistics, and lexical differences. It evaluates the scholarly contributions of major editors and researchers, including Hamid Sulaymonov and later editorial teams, emphasizing the importance of critical text preparation based on multiple manuscript sources. Overall, the research argues that Navoi’s Persian legacy is a significant part of both Persian and Turkic literary traditions, and that the establishment of a reliable critical edition of the Divan-i Fani remains an ongoing scholarly necessity.